2022
DOI: 10.1111/irv.13025
|View full text |Cite
|
Sign up to set email alerts
|

Level of maternal antibodies against respiratory syncytial virus (RSV) nucleoprotein at birth and risk of RSV very severe lower respiratory tract infection

Abstract: Background: The nucleoprotein (N protein) of respiratory syncytial virus (RSV) is a candidate antigen for new RSV vaccine development. The aim of the present study was to investigate the association between maternal antibody titers against the RSV N protein at birth and the newborns' risk of developing very severe lower respiratory tract infection (VS-LRTI).Methods: In this single-center prospective cohort study, 578 infants born during the RSV epidemic season in France were included. Among these, 36 were hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…For the secondary analysis, where children of all ages with or without the presence of significant comorbidities were included, an additional 34 studies were identified. 27–60 While most were undertaken in Europe (n = 19) 27–44,59 and North America (n = 6), 45–50 there was representation from Africa/Middle-East (n = 6) 51–54,58,60 and Australasia (n = 3). 55–57 Six focused on preterm, 33,35,40,41,43,46 23 covered both preterm and term 27–32,34,36–39,42,45,47,50–52,54–59 and 5 did not report gestational age.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the secondary analysis, where children of all ages with or without the presence of significant comorbidities were included, an additional 34 studies were identified. 27–60 While most were undertaken in Europe (n = 19) 27–44,59 and North America (n = 6), 45–50 there was representation from Africa/Middle-East (n = 6) 51–54,58,60 and Australasia (n = 3). 55–57 Six focused on preterm, 33,35,40,41,43,46 23 covered both preterm and term 27–32,34,36–39,42,45,47,50–52,54–59 and 5 did not report gestational age.…”
Section: Resultsmentioning
confidence: 99%
“…27–60 While most were undertaken in Europe (n = 19) 27–44,59 and North America (n = 6), 45–50 there was representation from Africa/Middle-East (n = 6) 51–54,58,60 and Australasia (n = 3). 55–57 Six focused on preterm, 33,35,40,41,43,46 23 covered both preterm and term 27–32,34,36–39,42,45,47,50–52,54–59 and 5 did not report gestational age. 44,48,49,53,60…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations